INFLUENCE OF ORGANIZATIONAL DESIGN, LEADERSHIP STYLE AND WORK CLIMATE TOWARD EMPLOYEE PERFORMANCE - Muhammad Ridwan; Achmad Fudholi; Edy Prasetyo Nugroho (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Performance  illustrates the achievement level of an activity, program or policy that is implemented in order to realize the goals, objectives, mission and vision of the organization as stated in the formulation of organization’s strategy. High performance is a necessity for an organization to be sustainable. The objective of this research was to determine the influence of organizational design, leadership style and work climate toward employee performance in PT. Kimia Farma Apotek Yogyakarta. The design of this study was cross sectional and analytical observation. Data were collected using a closed questionnaire. The samples were selected by census method. The number of population available as respondents was 160 people, but only 121 of them completed the questionnaire. The result of multiple linier regression analysis showed that there was a positive and significant impact between organizational design, leadership style, work climate and employee’s performance (the calculated F value (14.342) > F table (2.68) and p = 0.000) with the effective contribution of 26.9%. This mean that the organizational design, leadership style, and work climate influence the employee’s performance. Partially, based on the results of the t-test analysis, the design of the organization had a positive and significant impact on employee’s performance (value (2.057) > t table (1.658) and p = 0.042) with the effective contribution of 8.2%. This means that the more effective the organizational design, the higher the employee’s performance. Furthermore, the results of the t-test analysis showed that leadership style had a positive and significant impact on employee’s performance (t count value (2.354) > t table (1.658) and p = 0.020) with the effective contribution of 6.1%. It means that the more effective leadership style, the higher the employee’s performance. The results of the t-test analysis showed that work climate had a positive and significant impact on employee’s performance (t count value (4.782) > t table (1.658) and p = 0.000) with the effective contribution of 19.9%. This means that the more favorable work climate, the higher the work performance of employees.Keywords: The organizational Design, Leadership Style, Work Climate, Employee’s Performance.